E-Books systems - Zeki, Akram M.; Ibrahim, Hazeeha; Senam, Shayma (IIUM Press, 2011)
This project is using an online-approach that can minimize the usage of three major things in our life; time, money, and energy. The main objective of this project is to ease the process of selling and buying book among International Islamic University (IIUM) community by replacing it gradually to online system. The Online Book Seller Finder system will be able to provide user with online buying, selling, and auctioning process. Online Book Seller Finder system will be able to benefit IIUM community in being more efficient.